HUBUNGAN PERUBAHAN STRATEGI KEBIJAKAN PERDAGANGAN AMERIKA SERIKAT DENGAN DEFISIT NERACA PERDAGANGAN BARANG DI ERA DONALD TRUMP - Shafa Nabila (2020)
This study discusses the relationship of changes in the United States trade policy strategy under Donald Trump's administration with the goods trade balance deficit that occurs. The phenomenon raised by the researcher is interesting because Trump in his campaign made the issue of the deficit in the trade balance of goods as one of the main agenda. In realizing his goals, Trump, through his America First program, made a number of inward looking policies such as imposing a tarifff of 10-30% on a number of commodities, rededicated "harmful" trade agreements such as the North Atlantic Free Trade Agreement, the withdrawal from the Trans Pacific Partnership to conduct a trade war with China. Trump has an understanding that these policies can overcome the problem of unfair trade experienced by the United States, but the the trade balance deficit in 2016 to 2019 has increased. This study will look at whether changes in trade policy strategies that are becoming protectionist and increasing trade deficits in goods trade are interconnected. The method used in this research is to use a descriptive qualitative paradigm. Whereas in collecting data, researchers use study documents or known as librarian research and by conducting in-depth interviews with predetermined sources, which are considered to have theoretical and practical capacity. After that the data is processed with interpretive analysis techniques to draw conclusions and formulate a model that will be made in this study. Key words: Trade Policy, Protectionist, Donald Trump, Trade Balance Deficit